Framing terrorism : the news media, the government, and the public - Norris, Pippa; Kern, Montague, 1942-; Just, Marion R. (Routledge, 2003)
Framing Terrorism argues that the September 11 attacks precipitated a critical shift in the predominant "news frame" used by the US mass media for understanding issues of national security, thereby altering perceptions of risk at home and abroad.